Education Special Services Management Manajemen Layanan Khusus Pendidikan - Ritman Hendra; Monadia Turrahmi (BADAN PENERBIT STIEPARI PRESS, 2022)
Education is a human right that must be fully protected and considered, starting from educational institutions and education policy makers. Because of the importance of an education, it is necessary to have a special education service management, so that the implementation of education at the educational institution is in accordance with the objectives of education, so that the process of providing services to all students is an important part of school-based management (SBM) to support learning activities run smoothly. efficient and effective. Amalia (2018). Services that generally exist in schools consist of educational services, library services, counseling guidance services, cafeteria services, dormitory services, transportation services, cooperative services, and student council services. In this study, three indicators will be discussed, namely concepts, principles and techniques of special education service management. This study uses a qualitative approach with the type of literature study. Data were collected from various journals according to the research topic through descriptive analysis. The results of this study, special education service management part of school-based management is able to provide the best service to students from all services, in order to achieve the goals of education.